Impact of crop producer price changes on quantities of woodland products collected by communal households in Chivi, Zimbabwe - Mutamba, M. (2002)
The Zimbabwe woodlands are an important part of the rural households' livelihood system as they meet requirements for food, energy, construction materials and cash. This study uses linear programming approaches to understand how households best allocate scarce resources in meeting their requirements for food, energy, construction materials and cash, from woodland resources and agricultural production. Based on these relationships further analysis is done to understand how changes in output prices of different commodities produced by these households will affect quantities of woodland products that are harvested. The data used for this study was mainly collected in a quetionnaire survey that covered ten villages in the Romwe community in Chivi Districts, southern Zimbabwe.